بنية التكرار في شعر عز الدين ميهوبي عولمة الحب عولمة النار انموذجا - مدلل, نجاح (University of Eloued جامعة الوادي, 2009)
يعد التكرار من أبرز الظواهر الفنية والأسلوبية في الدراسات ال معاصرة ، ذلك أنه يحقق قيمة إبداعية وجمالية في الخطاب الأدبي ، ومن شأنه أن يكشف لنا عن المضامين الحقيقية الكامنة وراء هذا الخطاب ، فقد يكون الخطاب تأكيدا لأمر ما ، أو تنبيها للمتلقي وقد يهدف أحيانا للتقرير والتبيين والتدليل . The repetition of the most substantive and stylistic phenomena in studies of contemporary It is the value of creativity and beauty in the literary discourse, and would be disclosed Us on the contents of the real causes of this speech, it may be the speech confirmation of the order, or notice of the intended recipients have been times of the report and Signifying And to demonstrate.
Keywords: بنية التكرار، شعر عز الدين ميهوبي، العولمة; The structure of repetition, Ezzedine Mihoubi's poetry, globalization